An Expeditious Assembly of 3,4-Benzannulated-8-oxabicyclo[3:2:1]octane Systems - Venkata Subba Raju, O.; Rami Reddy, Y.V. (Asian Journal of Chemistry, 2013)
Substituted diarylmethylidenefluorene derivatives are generally synthesized by addition of fluorenylidene anions to benzophenone and subsequent dehydration and very recently using Peterson olefination.